The Effect Of Collaborative Learning Model Combined with Video Media on Senior High School Student’s Critical Thinking Skill and Biology Learning Outcomes in Regional Coffee Plantation Schools in Jember City - Ersa Setia Pratiwi; Suratno Suratno; Bea Hana Siswati (Bioedukasi: Jurnal Pendidikan Biologi, 2023)
The characteristics of students who go to school in a coffee plantation environment tend to be less active in learning, resulting in student saturation and low cognitive learning outcomes of students. This study aims to analyze the effect of collaborative learning models combined with video media on critical thinking skills and biology learning outcomes of class X SMAN Jenggawah with a quasi-experimental research type using a pre-test post-test control group design. The learning design by forming the class into small groups observing videos of arthropods found in the coffee plantation environment. Data collection was obtained from the implementation of observations, tests, and questionnaires. Data analysis was tested using the ANACOVA test for critical thinking skills and learning outcomes in the cognitive domain of students, and independent sample t-test for learning outcomes in the affective and psychomotor domains of students. The results showed a significance value of 0.000 <0.05 in critical thinking skills and a significance value of 0.001 <0.05 in learning outcomes in the cognitive domain, so the collaborative learning model had a significant effect on critical thinking skills and learning outcomes in the cognitive domain of class X high school students in coffee plantation area. Meanwhile, a significance value of 0.126 > 0.05 in the affective domain of learning outcomes, and a significance value of 0.213 > 0.05 in the psychomotor domain of learning outcomes, so that the collaborative learning learning model has no significant effect on critical thinking skills and cognitive learning outcomes of class X students high school in a coffee plantation area.